(untitled) (Journal of Biochemistry, Microbiology and Biotechnology, 2025)
A critical bioremediation effort is required to restore the phosphorus balance and improve water quality in polluted river sediments. Inorganic phosphate-solubilizing bacteria IPSB) play a vital role by releasing phosphate from organic matter, which helps reduce sediment accumulation and harmful algal blooms. This study aimed to isolate and identify indigenous strains of Curtobacteria and Bacillus isolated from Langat River sediments to assess their potential for phosphate solubilization and removal. Thirty (30) sediment samples collected between November 2022 and December 2023 at 10 different sampling stations (S1-S10) across the river were screened for phosphate solubilisation, extracellular phosphatase activities, and 16S rDNA gene sequencing. Fifty-eight (58) of the 83 isolated from the initial screening on nutrient agar medium exhibited a significant phosphate solubilization index (PSI), of which 31 isolates were able to decrease acid to release soluble reactive phosphorus (mg/L). S81B and S92G isolates demonstrated significant phosphate removal efficiencies of 64% and 62%, respectively. S81B exhibited higher acid phosphatase activity, while S92G showed more significant alkaline phosphatase activity, suggesting their adaptability to different pH conditions. Phylogenetic analyses revealed that S81B is closely related to Curtobacteria species, known for phosphorus mobilization in nutrient-limited environments, while S92G was similar to Bacillus, often associated with phosphorus cycling in soil and river ecosystems. These findings highlight the potential of these native strains for bioremediation applications to address phosphorus scarcity and mitigate eutrophication in the Langat River system.